(untitled) (Training and Practice : Journal of Educational Sciences, 2015)
The study shows how national defence education has been restored to general and higher education with the help of certain efforts, methods. It was marginalized due to the abolishment of the compulsory military service and as a result of it a kind of social undervaluation has appeared. The restoration of national defence education in schooling has been greatlysupported by the new teaching-learning method: distance learning. Our research was conducted by mapping the educational system of the two educational levels. We examined the two well-functioning educational sub-systems of national defence education. In the civilian higher education, we checked the attitude of the students studying National Defence Basics towards the subject and the method of e-learning by a survey and we found out that we need to create a large number of various online materials, worksheets and mock exam opportunities for a more effective learning.